Gastrointestinal Basidiobolomycosis (GIB) in Jeddah, Saudi Arabia - Muhammad Sohaib Ejaz Khan, Reem H Jabbad, Sanaa Fageeh, Nada Rabie, Abdullah H Jabbad, (Pakistan Journal of Medical & Health Sciences, 2023)
Basidiobolomycosis is a well known, but rare and under diagnosed condition. It is adeep-seated fungal infection caused by the organism Basidiobolusranarum a worldwide environmental saprophyte belonging to the Entomophthorales order of the class zygomycetes1,2 and is found in soil, decaying plants,and gastrointestinal tracts of amphibians, reptiles, horses, dogs and bats. It has been found to be of higher incidence in males (a male to female ratio of 11:1) and is seen in different age groups, the mean age being 37 years2. Eidam first isolated Basidiobolusranarum in 18863,9. Unlike other fungi, Basidiobolus Ranarum, can cause significant disease in the immune-competent hosts4.